Advancing Understanding of Global Mass Murder: A Comparison of Public Mass Stabbings and Shootings - Silva, Jason (Homicide studies, 2026)
Previous studies of global mass murder focus on public mass shootings, but there is little known about incidents involving other weapon types. To fill this gap in research, this study examines public mass stabbings and compares them with public mass shootings around the world (1999–2022). Findings identify significant differences in the geographic locations, target locations, offenders’ age and resolution, and number of victim casualties that illustrate these are unique forms of mass murder. This work provides the next step toward advancing knowledge of global mass murder and paves the way for future research aimed at understanding and addressing the phenomenon.